“Lost Inside Empire”: Self-Orientalization in the Animation and Sounds of Hayao Miyazaki’s The Wind Rises - Merchant-Knudsen, Travis R. (SARE: Southeast Asian Review of English, 2020)
Japan as a colonial power at the beginning of the twentieth century fell outside of the Eurocentric empires of the West. However, the country found itself preoccupied with ways of elevating its status in the hope of being equal to and, eventually, surpassing the West. The Wind Rises (2013), an anime film written and directed by Hayao Miyazaki, tells the story of Jiro Horikoshi, an aeronautical engineer who created the Mitsubishi A6M Zero used by the Japanese Empire during World War II. The animation and the sound design of the film are two formal elements that paint Jiro as a pacifist with a desire to create airplanes. It is a portrayal of an individual aspiring to be disparate from a colonial power, but the narrative suggests that it is, perhaps, impossible to completely align oneself outside of the imperial force of the Japanese Empire. The article explores how The Wind Rises, through the formal elements of anime and its sound design, carefully navigates Japan’s historical and colonial tensions.